Investigating the Successful Experiences of Countries in Employing Nurse Practitioners to Provide Primary Health Care: Recommendations for Iran - Masoumeh Rostami; Sasan Navkhasi; Majid Barati; Mohammad Hosein Sattari (Iran University of Medical Sciences, 2024)
Health systems are responsible for improving people's health and protecting them against the financial costs of illness while respecting their dignity and status. In recent decades, the health systems of developing countries have put extensive reform programs on their agenda to meet the growing needs of patients.